Transforming Dental Care: Integrating Geriatric Dentistry, Gerodontology, and Digital Marketing in Public Health - Asanza, Dachel Martínez; Njoku, Anuli U.; Baviskar, Snehal; Mouloudj, Farida; Asanza, Dachel Martínez; Njoku, Anuli U.; Baviskar, Snehal; Mouloudj, Farida (Digital Marketing for Public Dental Health: Global Impact Strategies, 2027)
The aging of the global population presents a significant challenge to public health, demanding innovative and sustainable dental approaches. This integrative literature review synthesizes research on the intersection of Geriatric Dentistry, Gerodontology, and digital marketing and communication str...
Archive Location: transforming-dental-care ISBN: 9798337388946

Oral Hygiene Care of Older Adults and Caregiver Education: A Systematic Review - Asanza, Dachel; Njoku, Anuli; Baviskar, Snehal; Evans, Marian; Mouloudj, Kamel (Hygiene, 2025)
Background: There is a need to develop comprehensive guidelines to encourage the promotion of oral hygiene care among older adults and to assist caregivers in this endeavor, taking into consideration the specific challenges that arise from aging, comorbidities and caregiving. Methods: This review was conducted by searching across relevant literature from meta-databases including Academic Google, PubMed, Scielo and Scopus for studies published from 2020 to 2024. PRISMA guidelines were followed. We included articles that described oral hygiene methods, caregiver education and mechanization status of older adults. Common themes, best practices, and gaps in current guidelines were tracked using extracted and analyzed data. Results: The review revealed multiple factors affecting the oral hygiene of older adults, with themes relating to physical impairment, cognitive dysfunction, and caregiver involvement. Highlighted between the approaches are individualized therapy for oral hygiene, caregiver education, and the use of technology to improve adherence to oral hygiene. Barriers like dental care access, underlying medical conditions complicating dental treatments, and cost considerations were identified. Conclusions: The findings emphasize the necessity of clear recommendations that can help caregivers and advance dental care for older adults.
Keywords: Dental care; Hygiene; MEDLINE; Oral health; Oral health care; Oral hygiene; Promotion (chess); Scopus; aged; caregiver education; caregivers; dentistry; dept.pch; education; frail elderly; healthy aging; older adult; oral health; oral hygiene; oral medicine

Determinants of Healthcare Professionals’ Intentions to Use Telemedicine for Elderly Care in Algeria: A Technology Acceptance Model Approach - Mouloudj, Kamel; Njoku, Anuli; Bouarar, Ahmed Chemseddine; Martínez Asanza, Dachel; Evans, Marian A.; Baviskar, Snehal (Geriatrics, 2026)
Background/Objectives: Telemedicine offers significant potential to improve the quality and accessibility of geriatric care, particularly in resource-constrained settings. However, its effective implementation depends largely on healthcare professionals’ acceptance and willingness to use such systems. Drawing on an extended Technology Acceptance Model (TAM), this study examines the determinants of doctors’ and nurses’ intentions to adopt telemedicine for elderly care in Algeria, with particular emphasis on self-efficacy and institutional support. Methods: This cross-sectional study employed a structured questionnaire administered to 130 healthcare professionals, including physicians and nurses, in Algeria. Hierarchical multiple regression analysis was conducted to test the proposed hypotheses and assess the incremental explanatory power of the extended model. Results: The extended TAM accounted for 48.7% of the variance in intention to use telemedicine. Institutional support (β = 0.432, p < 0.001) and self-efficacy (β = 0.264, p = 0.001) emerged as the strongest predictors. Perceived ease of use (β = 0.178, p = 0.038) and perceived usefulness (β = 0.139, p = 0.021) also had significant positive effects. The inclusion of self-efficacy and institutional support increased the model’s explanatory power by 23.5%. Conclusions: The findings highlight the critical role of organizational support mechanisms, digital competencies, and system usability in fostering telemedicine adoption among healthcare professionals. The study provides practical implications for policymakers and healthcare institutions, emphasizing the need for targeted training programs, supportive infrastructure, and institutional policies that enhance confidence and facilitate the integration of telemedicine into clinical workflows.
Keywords: Algeria; Technology Acceptance Model (TAM); cross-sectional study; dept.pch; digital health; elderly care; healthcare professionals; institutional support; self-efficacy; telemedicine

Investigating antecedents of intention to use green agri-food delivery apps: merging TPB with trust and electronic word of mouth - Mouloudj, Kamel; Aprile, Maria; Bouarar, Ahmed; Njoku, Anuli; Evans, Marian; Oanh, Le; Asanza, Dachel; Mouloudj, Smail (Sustainability, 2025)
The rapid expansion of digital platforms has significantly influenced consumer purchasing behaviors, particularly in the agri-food sector. Therefore, this paper investigates the key factors driving customers’ intention to use green agri-food delivery apps (GAFDAs) by integrating trust and electronic word of mouth (eWOM) into the Theory of Planned Behavior (TPB) framework. Additionally, this study examines gender as a moderating variable, assessing whether its influence alters the relationships between key determinants and behavioral intention. Data were collected from 252 Algerian consumers, and the proposed model was tested using SmartPLS 4 and SPSS 26.0. The results confirm that attitude, subjective norms, perceived behavioral control (PBC), trust, and eWOM positively and significantly influence the intention to use GAFDAs, with PBC emerging as the strongest predictor. Moreover, gender moderates the effect of trust on behavioral intention, with trust significantly influencing men’s adoption decisions but not those of females. In contrast, subjective norms and PBC are stronger predictors for female consumers. These findings highlight the importance of gender-specific marketing strategies to enhance GAFDA adoption. This study contributes to the literature by extending TPB with trust, eWOM, and gender moderation, offering valuable insights for marketers, policymakers, and app developers promoting sustainable food consumption.
Keywords: Advertising; Artificial intelligence; Business; Computer science; Control (management); Food delivery; Marketing; Psychology; Theory of planned behavior; Word of mouth; dept.pch

Modeling predictors of medication waste reduction intention in Algeria: extending the theory of planned behavior - Mouloudj, Kamel; Njoku, Anuli; Asanza, Dachel Martínez; Bouarar, Ahmed Chemseddine; Evans, Marian A.; Mouloudj, Smail; Bouarar, Achouak (International Journal of Environmental Research and Public Health, 2023)
COVID-19 caused an increase in the demand for medications, which led to an increase in pharmaceutical waste and there is no doubt that this contributes to environmental pollution. Hence, it became necessary to search for how to protect and improve the environment by encouraging the behavior of medication waste reduction. Accordingly, this study aims to investigate the factors affecting intentions to reduce medication waste. Considering this, we develop an extended theory of planned behavior (TPB) framework by incorporating the constructs of moral obligation, environmental awareness, and medication waste risk perception. Using the convenience sampling method and based on a self-administered questionnaire, a total of 225 usable responses were collected in five Algerian cities. The results showed that positive attitudes (β = 0.316, p < 0.001), moral obligation (β = 0.291, p < 0.001), environmental awareness (β = 0.227, p < 0.001), perceived behavior control (PBC) (β = 0.151, p = 0.001), greater perceived risks (β = 0.127, p < 0.001), and subjective norm (β = 0.096, p < 0.05) significantly and positively influence the medication waste minimization intention. Furthermore, our analyses revealed that the extended TPB model explained 73.40% of the intention variance. In conclusion, we have explored the intentions, and there may be a gap between intent and actual behavior. Therefore, we recommend future studies to examine the factors affecting the actual behavior of medication waste reduction and to investigate environmental ethics and religious commitment as predictors of waste reduction intentions.
0 citations (Crossref) [2023-10-31] Number: 16
Keywords: Africa; dept.pch; environmental health; environmental pollution; medication ecotoxicity; medication waste; moral obligation; peer-reviewed; perceived risk; pharmaceutical waste; theory of planned behavior; unused medications

Social Marketing for Health Equity: Promoting Preventive Health Behavior Among Women in Rural Communities - Mouloudj, Kamel; Alameri, Sarah Ali Saeed; Evans, Marian A.; Almado, Alaa Abdulkareem Ghaleb; Mahmoud, Basheer Ismail; Asanza, Dachel Martínez (International Journal of Environmental Research and Public Health, 2026)
Preventive health behaviors play a critical role in reducing disease risks and improving public health outcomes, particularly among vulnerable populations such as women in rural communities. However, limited research has explored the determinants of intentions to adopt preventive health behaviors in developing contexts among women in rural communities. This study applies and extends the Theory of Planned Behavior (TPB) to examine these determinants in Algeria. A cross-sectional study was conducted using convenience sampling among 205 women in rural communities aged 20–60 years across five Algerian cities. Data were collected through a self-administered questionnaire and analyzed using hierarchical multiple regression. The results indicate that attitude, subjective norms, and perceived behavioral control have significant positive effects on behavioral intention. The inclusion of health literacy significantly enhances the model’s explanatory power, with higher literacy associated with stronger intentions. In contrast, perceived healthcare discrimination does not have a statistically significant effect. The extended model explains 57.5% of the variance in behavioral intention. These findings underscore the importance of psychosocial and informational factors in shaping preventive health intentions and support the extension of TPB in this context. They also provide practical implications for policymakers and healthcare practitioners to design targeted social marketing interventions aimed at improving preventive health behaviors and reducing health disparities among women in rural communities. © 2026 by the authors.
Keywords: Behavior change; Health belief model; Health care; Health literacy; Health promotion; Psychological intervention; Psychosocial; Public health; Social marketing; Theory of planned behavior; dept.pch; health equity; health literacy; health policy; perceived healthcare discrimination; preventive health behaviors; women in rural communities

Factors influencing the adoption of digital health apps: an extended technology acceptance model (TAM) - Mouloudj, Kamel; Bouarar, Ahmed Chemseddine; Asanza, Dachel Martínez; Saadaoui, Linda; Mouloudj, Smail; Njoku, Anuli U.; Evans, Marian A.; Bouarar, Achouak (Integrating Digital Health Strategies for Effective Administration, 2023)
Mobile health apps have been widely considered in the healthcare sector as innovative channels to reach patients and their families. Accordingly, the aim of the chapter was to investigate factors that influence the customers' adoption of digital health apps in Algeria. The authors adopted an extende...
Keywords: dept.pch